Fixed Point and Best Proximity Point Results for Generalised Cyclic Coupled Mappings: J. Geno Kadwin, M. Marudai - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, by introducing the new concept called cyclic coupled proximal mappings we explore the existence of strong coupled best proximity point in metric spaces that generalizes the results of [1]. Further, we also proved the existence of strong coupled fixed point for multi-valued cyclic coupled mapping under suitable conditions.